2022
DOI: 10.15625/1811-4989/16365
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Citrus limon peel extraction, determination of main chemical components and effectiveness in repellency against Aedes mosquito dengue fever vector

Abstract: Currently, scientific publications are focusing on the pharmacological actions of Citrus limon's extract and essential oil. Its essential oil is rich in bioactive monoterpenoids, such as D-limonene, β-pinene, γ-terpinene. Citrus limon essential oils have been recognized as the potential source of natural insecticides because of their selectivity, ability to be biologically degraded into non-toxic compounds, low impacts on biodiversity and the environment. Many previous studies have reported anti-bacterial, ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…These results could possibly be attributed to the presence of the monoterpenoid D-limonene as the main component in the ethanolic extract. This is because in essential oils from a species of the same genus (Citrus limon), this component has been identified as the most prevalent and recognized as a bioactive compound with potential insecticidal effects [17].…”
Section: Resultsmentioning
confidence: 99%
“…These results could possibly be attributed to the presence of the monoterpenoid D-limonene as the main component in the ethanolic extract. This is because in essential oils from a species of the same genus (Citrus limon), this component has been identified as the most prevalent and recognized as a bioactive compound with potential insecticidal effects [17].…”
Section: Resultsmentioning
confidence: 99%
“…Deletre et al 2013 reported the repellent properties of 20 essential oils against malaria vector. Many studies have proven that limonene extracted from citrus peel was a fragrance agent (Singh et al, 2021), limonene created fragrance and also used for mosquitoes repelled application (Hue et al, 2022). Similarly, Phasomkusolsil and Soonwera (2016), demonstrated that formulation consisted of Cymbopogon citratus (lemon grass), Syzygium aromaticum (cloves), essential oils indicated high repellency, among them strong effective repellency was observed by lemongrass by using arm in cage method.…”
Section: Discussionmentioning
confidence: 99%